Structural and vibrational study of cubic Sb2O3 under high pressure - Pereira, A. L. J. [UNESP]; Gracia, L.; Santamaria-Perez, D.; Vilaplana, R.; Manjon, F. J.; Errandonea, D.; Nalin, M.; Beltran, A. (Amer Physical Soc, 2012)
We report an experimental and theoretical study of antimony oxide (Sb2O3) in its cubic phase (senarmontite) under high pressure. X-ray diffraction and Raman scattering measurements up to 18 and 25 GPa, respectively, have been complemented with ab initio total-energy and lattice-dynamics calculations. X-ray diffraction measurements do not provide evidence of a space-group symmetry change in senarmontite up to 18 GPa. However, Raman scattering measurements evidence changes in the pressure coefficients of the Raman mode frequencies at 3.5 and 10 GPa, respectively. The behavior of the Raman modes with increasing pressure up to 25 GPa is fully reproduced by the lattice-dynamics calculations in cubic Sb2O3. Therefore, the combined analysis of both experiments and lattice-dynamics calculations suggest the occurrence of two isostructural phase transformations at 3.5 and 10 GPa, respectively. Total-energy calculations show that the isostructural phase transformations occur through local atomic displacements in which senarmontite loses its molecular character to become a three-dimensional solid. In addition, our calculations provide evidence that cubic senarmontite cannot undergo a phase transition to orthorhombic valentinite at high pressure, and that a phase transition to a beta-Bi2O3-type structure is possible above 25 GPa.